Penentuan Kadar Meloksikam Sediaan Tablet Dari Berbagai Apotek Yang Terdapat Di Rantau Prapat Secara Spektrofotometri – UV - Risma Fauziah Pasaribu; Anny Sartika Daulay; Ridwanto Ridwanto; Rafita Yuniarti (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Meloxicam is a non-steroidal anti-inflammatory drug that can relieve arthritis symptoms, such as inflammation, swelling, and muscle stiffness and pain, by acting as an inhibitor of enzymes that produce prostaglandins. In the Indonesian Pharmacopoeia Edition V (2014), the determination of sugar tablet content was carried out using high performance liquid chromatography. This method is expensive compared to the spectrophotometric method. The purpose of this research is to find an alternative method that is simple and inexpensive but provides good accuracy. This research was descriptive in nature using spectrophotometry-UV method, with 0.1 N NaOH Methanol as a solvent. The samples used in this study were 4 generic meloxicam tablets. The test parameters of this research included the preparation of Standard Mother Solution I (LIB I). Maximum wavelength, Linearity Protection of the Calibration Curve and Determination of the Concentration of Meloxicam in Tablet Preparations. From the results of testing the samples, generic meloxicam tablets were taken from PT. (Dankos pharma) 102.47 ± 0.9868%; generic meloxicam tablets (PT. Etercon Pharma) 98.05 ± 1.0930%; generic meloxicam tablets (PT. Mahakam Beta Farma) 99.79 ± 1.046%; generic tablets (Triman) 101.21 ± 2.4345%. All the tablets specified meet the general strength requirements, that is, the active ingredient content is not less than 90% and not more than 110% of the amount stated on the label.